Isolation and Identification of Mycorrhizosphere Bacteria and Their Antagonistic Effects Towards Ganoderma boninense in vitro - YENNI BAKHTIAR; SUDIRMAN YAHYA; WAHONO SUMARYONO; MEITY SURADJI SINAGA; SRI WILARSO BUDI; TEUKU TAJUDDIN (Indonesian Society for microbiology, 2010)
Basal stem rot caused by Ganoderma boninense is the most serious disease of oil palm (Elaeis guineensis) in Indonesia and it has caused major loss in palm oil production. Mycorrhizosphere bacteria offer possible advantages as biocontrol agents as they live and proliferate together with arbuscular mycorrhizal fungi, which have an ability to increase plant resistance against pathogens. A study was conducted to isolate mycorrhizosphere bacteria from spores of arbuscular mycorrhizal fungi and test their antagonistic effects against G. boninense in vitro. All bacterial isolates were identified based on 16S rDNA analysis and it revealed that eleven out of twenty mycorrhizosphere bacteria isolated were related to Bacillus with similarity ranging from 97 to 100%, whereas other isolates were identified as Pseudomonas, Streptomyces, Kocuria, Enterobacter, Brevundimonas, and Alcaligenes with similarities ranging from 96 to 100%. Fourteen out of twenty mycorrhizosphere bacteria showed a varying degree of inhibition towards the growth of G. boninense in vitro. Of these, isolate B10 (closely related to Bacillus subtilis ZJ06) showed the highest inhibitory effect followed by B17 (closely related to Bacillus subtilis N43). Therefore, these bacteria have a potential to be used as biocontrol agents to control basal stem rot disease caused by G. boninense in oil palm.